2007
DOI: 10.1016/s0873-2159(15)30361-5
|View full text |Cite
|
Sign up to set email alerts
|

Bronquiolite obliterante pós-infecciosa na criança

Abstract: Bronchiolitis obliterans (BO) is a rare disease in immunocompetent children that usually occurs after infection of the lower airways. While a diagnosis of BO was usually confirmed by lung biopsy, identification of prior lung lesion plus a typical clinical course and a suggestive chest X-ray and CT scan have replaced the need for more invasive procedures. The authors reviewed the clinical records of 10 BO patients, followed in the Outpatients Paediatric Pulmonology Unit from January 1997 to December 2002, to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
5
0
6
Order By: Relevance
“…The data collected in this study for diagnosis age and early clinical signs are similar to those found in other studies, which featured diagnosis ages ranging from 1 month-old to 3 years-old, 4,8,23 while the first respiratory signs are always seen before the age of 2 4 and the disease was most frequent among boys. 7,8,23 In this study, most of the population consisted of white children, which apparently follows the characteristics of the general population from which it was sampled.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The data collected in this study for diagnosis age and early clinical signs are similar to those found in other studies, which featured diagnosis ages ranging from 1 month-old to 3 years-old, 4,8,23 while the first respiratory signs are always seen before the age of 2 4 and the disease was most frequent among boys. 7,8,23 In this study, most of the population consisted of white children, which apparently follows the characteristics of the general population from which it was sampled.…”
Section: Discussionsupporting
confidence: 86%
“…Though these needs are specific for each individual, the ultimate goal is to allow them to grow properly for their age. 2,4 The few studies available [4][5][6][7][8] which describe the nutritional status of BO patients are inconsistent in their methods and do not explore the nutritional status of the individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos realizados em indivíduos com bronquiolite obliterante 3,5 , mesmo sem detalhar os métodos de diagnóstico nutricional, apontam a desnutrição como um achado frequente.…”
Section: I S C U S S ã Ounclassified
“…Embora essas necessidades devam ser individualizadas, o objetivo é manter o crescimento adequado para a idade do indivíduo 2,4 .…”
Section: Introductionunclassified
“…Os poucos estudos disponíveis na literatura [4][5][6][7][8] que referem a condição nutricional de pacientes com BO são inconsistentes quanto aos métodos utilizados e não exploram a condição nutricional destes indivíduos, mas são unânimes quanto à atenção dispensada na recuperação e/ou preservação do estado nutricional nesta condição clínica e ao reconhecer as implicações que o déficit nutricional pode trazer na evolução da doença.…”
Section: Introductionunclassified